HUBUNGAN PENGGUNAAN BUKU PENGHUBUNG GURU-ORANG TUA DAN EFEKTIVITAS KOMUNIKASI PEMBELAJARAN SISWA TERHADAP PRESTASI BELAJAR IPA DI SD INPRES PARANG KOTA MAKASSAR - Selvi, Nurhayati (AIJER, 2019)
Abstract: The Relationship between the Use of Teacher-Parental communicator book and the Effectiveness of Student Learning Communication on Natural Science Learning Achievement at SD Inpres Parang Makassar. This study aimed (1) to look at the relationship between the use of parent-student communicator book on science learning achievement (2) to see the relationship between the effectiveness of student communication and science learning achievement (3) to see the relationship between the use of parent-student communicator book and student communication effectiveness on science learning achievement. The research used ex post facto research method. Data collection techniques were questionnaires for parent-student communicator book variables and the effectiveness of learning communication and documentation of science learning achievement variables. The population was all elementary school students of SD Inpres Parang Makassar, consisted of 66 students in even semester Academic Year 2018. The sampling technique was purposive sampling with 57 students. The data analysis technique was descriptive and inferential analysis. The results showed that there was a positive relationship between the use of communicator book and the learning achievement of science in SD Inpres Parang Makassar, but had weak relationship. There was a positive relationship between the effectiveness of student learning communication on science learning achievement in SD Inpres Parang Makassar, with moderate relationship. There was a positive relationship between the use of communicator book and the effectiveness of student learning communication on science learning achievement in SD Inpres Parang Makassar, the relationship among three variables was moderate.Keywords: Communicator book, Learning communication, Science Learning Achievement